2018
DOI: 10.11152/mu-1562
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Cone Beam Computed Tomography and ultrasonography with two types of probes in the detection of opaque and non-opaque foreign bodies

Abstract: Aim: The aim of this study was to compare the diagnostic accuracy of intra-oral and extra-oral ultrasonographic (US) examinations performed with linear and convex probes in the detection of opaque and non-opaque foreign bodies (FBs) located in the maxillofacial area.Materials and methods: Thirteen different type of FBs were inserted into a sheep’s head: a) on the external bone surface of mandible (between the mandibular corpus and masseter muscle), b) in the intrinsic muscular tissue (in the dorsum of the tong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
1
2
1
Order By: Relevance
“…1,10 The extra-oral and intra-oral linear probes were employed by Aras et al and Demiralp to find FBs. 1,5 In this study, we observed that the data of the linear and hockey probes are similar. Additionally, there was no difference between the measurements visualized by both probes and their actual dimensions (p>0.05).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…1,10 The extra-oral and intra-oral linear probes were employed by Aras et al and Demiralp to find FBs. 1,5 In this study, we observed that the data of the linear and hockey probes are similar. Additionally, there was no difference between the measurements visualized by both probes and their actual dimensions (p>0.05).…”
Section: Discussionsupporting
confidence: 57%
“…However, the first line of defense for detecting low-radiodensity foreign entities confined in soft tissue should be US using a linear probe. 5 Ultrasonography is a great alternative if the missing oral foreign body is in the easily accessible superficial soft tissue of the head and neck region. But, it might not be appropriate for FBs located in deep areas or air-filled cavities.…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Demiralp et al on FBs in intraoral localization conducted with phantoms, they reported a hypoechoic halo around the FBs in the case of chicken bone fragment, root, stone, tooth enamel, amalgam, and orthodontic wire stab [11]. In our study, only the chicken bone fragment was examined among these FBs, and we did not observe a hypoechoic halo around it.…”
Section: Discussioncontrasting
confidence: 47%
“…A combination of radiography and ultrasonography (oral and/or an inter‐mandibular approach) often provides the most accurate information regarding the presence and localisation of foreign bodies in the tongue. If the diagnosis of a suspected foreign body in the mouth is not possible with either radiography or ultrasound, a CT or MRI examination of the head should be considered (Chiyonobu et al 2015; Demiralp et al 2018).…”
Section: Discussionmentioning
confidence: 99%